Autocad 2012 for dummies - Byrnes, David (Hoboken, NJ : Wiley Pub., Inc., 2011)
An introduction to the drafting software covers every aspect of this program, from the basics to more advanced applications, and furnishes the latest features, including Internet-driven design capabilities.
Includes index.
Keywords: AutoCAD; AutoCAD (Computer software); Computer-aided design; Computer graphics